THE USE OF ARTICULATION LEARNING MODELS IN PAI SUBJECTS AT SMPN 1 PONTANG - Wasehudin, Wasehudin; Anshori, Irfan; Hasanah, Uswatun (TARBAWY: Indonesian Journal of Islamic Education, 2022)
Abstract The educational process in the pandemic era requires it to be carried out online. This study aims to determine the learning process of Islamic religious education, either in terms of strengths, weaknesses, opportunities or threats that occur in educational institutions that implement online learning. The research was conducted at Junior High School (SMP) Negeri 1 Tirtayasa, Serang Regency, Banten. By using observation and interview techniques, it can be concluded that the strength of the online learning process is that it can be carried out with flexible time, does not require a special place to make it easier for students to have discussions with parents. The downsides are the unstable internet network and limited internet quota. Opportunities from online learning are to train students to be independent in learning, to train students’ skills and skills in the realm of device skills. Meanwhile, the threats identified included a decrease in students’ eyesight, absorption of understanding, and a decline in student’s moral due to a lack of supervision.Abstrak Proses pendidikan di era pandemic mengharuskan untuk dilakukan secara daring. Penelitian ini bertujuan untuk mengetahui proses pembelajaran pendidikan agama Islam, baik dari aspek kekuatan, kelemahan, peluang hingga ancaman yang terjadi pada lembaga pendidikan yang menerapkan pembelajaran secara daring. Penelitian ini dilakukan di Sekolah Menengah Pertama (SMP) Negeri 1 Tirtayasa Kabupaten Serang, Banten.  Dengan menggunakan teknik observasi dan wawancara maka dapat disimpulkan bahwa kekuatan dalam proses belajar secara daring yaitu dapat dilangsungkan dengan waktu yang fleksible, tidak membutuhkan tempat khusus hingga memudahkan siswa menjalin diskusi dengan orangtua. Kelemahannya yaitu jaringan internet yang tidak stabil dan kuota internet yang terbatas. Peluang dari pembelajaran daring yaitu melatih siswa agar mandiri dalam belajar, melatih skill dan keterampilan siswa pada ranah keterampilan perangkat. Sedangkan ancaman yang teridentifikasi di antaranya menurunnya daya penglihatan siswa, daya serap memahami, hingga merosotnya moral siswa karena minimnya pengawasan.